Skeletal muscle characterization of Japanese quail line selectively bred for lower body weight as an avian model of delayed muscle growth with hypoplasia. - Young Min Choi; Yeunsu Suh; Sangsu Shin; Kichoon Lee (PLoS ONE)
This study was designed to extensively characterize the skeletal muscle development in the low weight (LW) quail selected from random bred control (RBC) Japanese quail in order to provide a new avian model of impaired and delayed growth in physically normal animals. The LW line had smaller embryo and body weights than the RBC line in all age groups (P<0.05). During 3 to 42 d post-hatch, the LW line exhibited approximately 60% smaller weight of pectoralis major muscle (PM), mainly resulting from lower fiber numbers compared to the RBC line (P<0.05). During early post-hatch period when myotubes are still actively forming, the LW line showed impaired PM growth with prolonged expression of Pax7 and lower expression levels of MyoD, Myf-5, and myogenin (P<0.05), likely leading to impairment of myogenic differentiation and consequently, reduced muscle fiber formation. Additionally, the LW line had delayed transition of neonatal to adult myosin heavy chain isoform, suggesting delayed muscle maturation. This is further supported by the finding that the LW line continued to grow unlike the RBC line; difference in the percentages of PMW to body weights between both quail lines diminished with increasing age from 42 to 75 d post-hatch. This delayed muscle growth in the LW line is accompanied by higher levels of myogenin expression at 42 d (P<0.05), higher percentage of centered nuclei at 42 d (P<0.01), and greater rate of increase in fiber size between 42 and 75 d post-hatch (P<0.001) compared to the RBC line. Analysis of physiological, morphological, and developmental parameters during muscle development of the LW quail line provided a well-characterized avian model for future identification of the responsible genes and for studying mechanisms of hypoplasia and delayed muscle growth.